2014
DOI: 10.1515/hsz-2014-0152
|View full text |Cite
|
Sign up to set email alerts
|

An ancient oxidoreductase making differential use of its cofactors

Abstract: Many transcription factors contribute to cellular homeostasis by integrating multiple signals. Signaling via the yeast Gal80 protein, a negative regulator of the prototypic transcription activator Gal4, is primarily regulated by galactose. ScGal80 from Saccharomyces cerevisiae has been reported to bind NAD(P). Here, we show that the ability to bind these ligands is conserved in KlGal80, a Gal80 homolog from the distantly related yeast Kluyveromyces lactis. However, the homologs apparently have diverged with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The different KlGAL80 alleles were generated by site-directed mutagenesis using the QuikChange Multi Site-Directed Mutagenesis Kit (Agilent Technologies) or by fusion PCR, verified by DNA sequencing, and introduced into JA6/D802 ( Klgal80::ScURA3 ) ( Zenke et al, 1993 ) as restriction fragments replacing Klgal80::ScURA3 . The S. cerevisiae strains FI4-s4 ScGAL80 ( ScGAL80 ) and FI4-s4 ScGAL80KR56A ( Scgal80-K5A, R6A ) were isogenic to FI4 sin4∆Scgal80∆ ( sin4::HIS5 Scgal80::ScURA3 ) ( Blueher et al, 2014 ) except for the indicated ScGAL80 alleles. The different GAL80 alleles were generated by site-directed mutagenesis using the QuikChange Multi Site-Directed Mutagenesis Kit (Agilent Technologies) or by fusion PCR, verified by DNA sequencing and introduced into FI4 sin4 ∆ Scgal80 ∆ as a PCR fragment replacing Scgal80::ScURA3 .…”
Section: Methodsmentioning
confidence: 99%
“…The different KlGAL80 alleles were generated by site-directed mutagenesis using the QuikChange Multi Site-Directed Mutagenesis Kit (Agilent Technologies) or by fusion PCR, verified by DNA sequencing, and introduced into JA6/D802 ( Klgal80::ScURA3 ) ( Zenke et al, 1993 ) as restriction fragments replacing Klgal80::ScURA3 . The S. cerevisiae strains FI4-s4 ScGAL80 ( ScGAL80 ) and FI4-s4 ScGAL80KR56A ( Scgal80-K5A, R6A ) were isogenic to FI4 sin4∆Scgal80∆ ( sin4::HIS5 Scgal80::ScURA3 ) ( Blueher et al, 2014 ) except for the indicated ScGAL80 alleles. The different GAL80 alleles were generated by site-directed mutagenesis using the QuikChange Multi Site-Directed Mutagenesis Kit (Agilent Technologies) or by fusion PCR, verified by DNA sequencing and introduced into FI4 sin4 ∆ Scgal80 ∆ as a PCR fragment replacing Scgal80::ScURA3 .…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have also shown that iPS cells generated by means of retroviral viruses generate teratomas . Cells can be reprogrammed with non‐integrating viruses such as the Sendai virus based system, however it requires a long time before transfected cells are vector‐free .…”
Section: Introductionmentioning
confidence: 99%